1973
DOI: 10.1007/bf03181016
|View full text |Cite
|
Sign up to set email alerts
|

The saints and the roughnecks

Abstract: Black and white, male and female, rich and poor, American teenagers have the herding instinct. On streetcorners, in shopping centers, in the ghetto and in the suburbs, the boys and the girls hang out. Sometimes the kids get together for fun, sometimes for trouble, sometimes for political purposes. Mostly, they crave recognition, companionship and excitement. Gangs are a way of life for many adolescents-part of the ritual of growing up.Eight promising young men-children of good, stable, white upper-middle-class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(63 citation statements)
references
References 0 publications
2
60
0
1
Order By: Relevance
“…In the end, our arguments serve to highlight the active role of offenders in the delinquency process as well as the ability of such youths to exercise manipulative power over adults in certain situations. When combined with the observations of conflict theorists (e.g., Chambliss 1973;Males 1999;Reiman 2004), our arguments also draw attention to important group differences in the ability to exercise manipulative power, including differences based on social class, race, gender, and age.…”
mentioning
confidence: 58%
“…In the end, our arguments serve to highlight the active role of offenders in the delinquency process as well as the ability of such youths to exercise manipulative power over adults in certain situations. When combined with the observations of conflict theorists (e.g., Chambliss 1973;Males 1999;Reiman 2004), our arguments also draw attention to important group differences in the ability to exercise manipulative power, including differences based on social class, race, gender, and age.…”
mentioning
confidence: 58%
“…For families with low socioeconomic status (SES), some research suggests that social class can affect the quality of parent-child relations; these families face more stressful circumstances that can limit parental expressions of affection, promote more punitive parenting, and inhibit children from seeing parents as role models (McLoyd & Wilson, 1992;Sampson & Laub, 1994). Families with greater resources, more influence, greater knowledge, and better connections are also better positioned to advocate for the advancement of their children as well as to protect them from negative circumstances or the consequences of bad behavior (Chambliss, 1973;Conley, 2001;Furstenberg, 2006;Lareau, 2003).…”
Section: Family Resources and Social Reproductionmentioning
confidence: 99%
“…This was demonstrated by early research conducted by Chambliss (1973) who found that police officers always took action against the group of people labelled the 'roughnecks' (those who had lower class backgrounds) when compared to the 'saints'…”
Section: Introductionmentioning
confidence: 99%